Radiation Therapy of Carcinoma of the Esophagus - Thomas J Keane (Canadian Journal of Gastroenterology)
Radical radiation therapy with curative intent for esophageal squamous carcinoma is used both as a single modality and combined with chemotherapy. Failure to eradicate disease at the primary tumour site represents the greatest cause of failure of curative radiotherapy. The aim of curative radiotherapy is to deliver the highest dose of radiation at the tumour site while minimizing radiation delivered to the surrounding tissues. The best survival results are obtained in patients with tumours less than 5 cm in length, confined to the upper one-third of the esophagus. Regular endoscopic examinations two to three times per year in the first two years post treatment should rule out the vast majority of treatment failures.